2013
DOI: 10.1177/030089161309900129
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Quality of Life, and Mood States during Chemotherapy in Italian Cancer Patients

Abstract: Aims and background In cancer patients, fatigue interferes with the individual's functioning and quality of life (QoL). We investigated the association between fatigue and the main QoL dimensions and mood states as well as the main sociodemographic and clinical variables. Methods A total of 105 inpatients undergoing chemotherapy were administered the Revised Piper Fatigue Scale and the EORTC QLQ-C30 and POMS questionnaires, along with a form for collecting personal and clinical data. Results Compared with pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
12
0
3
Order By: Relevance
“…The important point is that disease associated with the β coefficient of 0.36 has more effect on mental health in comparison with other independent variables and clinical symptoms with 0.35 of impact coefficient has a direct effect on life quality. Physical health and mental health with 0.15 and 0.14 of β coefficient, respectively affected the life quality (Ghanbari et al, 2010;Annunziata et al, 2013). Study of Abedi et al (2012) showed that physical health with 0.224 β coefficients had the highest effective and environmental health with 0.242 β coefficients the lowest effect on the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The important point is that disease associated with the β coefficient of 0.36 has more effect on mental health in comparison with other independent variables and clinical symptoms with 0.35 of impact coefficient has a direct effect on life quality. Physical health and mental health with 0.15 and 0.14 of β coefficient, respectively affected the life quality (Ghanbari et al, 2010;Annunziata et al, 2013). Study of Abedi et al (2012) showed that physical health with 0.224 β coefficients had the highest effective and environmental health with 0.242 β coefficients the lowest effect on the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is associated with a reduction in QoL with worse functioning in all domains for cancer patients [29]. In a study of 109 older patients undergoing chemotherapy, fatigue and financial impact caused the most distress followed by anxiety and depression [30].…”
Section: Fatiguementioning
confidence: 99%
“…These effects are due not only to the disease itself but also to therapies administered to treat it. Chemotherapy is one of the major therapeutic options for solid and haematological tumours and is often associated with unpleasant side effects such as nausea/vomiting (Hesketh, ; Janelsins et al., ; Warr, ), fatigue (Annunziata, Muzzatti, Mella, & Bidoli, ; Koornstra, Peters, Donofrio, van den Borne, & de Jong, ; Weis, ), loss of appetite (Boltong, Keast, & Aranda, ; Boltong et al., ; Dobrila‐Dintinjana et al., ), hair loss (Chon, Champion, Geddes, & Rashid, ; Lemieux, Maunsell, & Provencher, ; Paus, Haslam, Sharov, & Botchkarev, ), altered bowel habits (Andreyev et al., ; Gibson & Keefe, ; Touchefeu et al., ), pain (Fallon, ; Pachman, Barton, Watson, & Loprinzi, ; Park, ), and depression (Ho, Rohan, Parent, Tager, & McKinley, ; Hwang, Chang, & Park, ; Polat, Arpacı, Demir, Erdal, & Yalcin, ). Some of these effects are acute and more frequent on the days immediately following drug administration, but many of them persist long after completion of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy side effects (CSE) have a considerable impact on quality of life (QOL) (Annunziata et al, 2013;Domati et al, 2015;Hwang et al, 2013;Mannion, Gilmartin, Donnellan, Keane, & Waldron, 2014;Wintner et al, 2013) and can severely impair a patient's ability to manage daily activities and employment. Moreover, unsatisfactory control of chemotherapy toxicities affecting treatment effectiveness necessitates dose reduction and/or treatment deferral (Havrilesky, Reiner, Morrow, Watson, & Crawford, 2015).…”
mentioning
confidence: 99%